DEVELOPMENT OF A MANAGEMENT SYSTEM FOR PASSENGER AND FREIGHT TRANSPORTATION IN RAIL TRANSPORT - Mamura Kushakova (Ecomind Press, 2025)
The development of an efficient management system for passenger and freight transportation in railway transport plays a crucial role in optimizing logistics, reducing costs, and enhancing service quality. In Uzbekistan, the railway sector is a fundamental component of the transportation infrastructure, necessitating advanced strategies to ensure sustainable development. This paper explores key management practices in railway transport, focusing on digitalization, operational efficiency, and customer-oriented approaches. It examines the challenges faced by the railway industry in Uzbekistan, including infrastructure limitations, financial constraints, and regulatory issues. Furthermore, the study highlights innovative solutions such as smart technologies, automated scheduling, and integrated logistics platforms that can improve both passenger and freight transport efficiency. By analyzing global best practices and their applicability to Uzbekistan’s railway system, this research provides insights into optimizing management strategies to meet growing transportation demands.